PENDIDIKAN KARAKTER SEBAGAI STRATEGI MENINGKATKAN DAYA SAING SISWA SEKOLAH DASAR DI ERA GLOBAL - Aulia Afriza, Gempita; Oktafia, Rahma; Elmalia, Suci; Fitria, Yanti; Kharisma, Inggria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education plays a crucial role in shaping the quality of elementary school students, equipping them to face the challenges of the globalization era. The increasingly rapid development of science and technology demands that students possess not only academic abilities but also strong attitudes, moral values, and social skills. This study aims to analyze the role of character education as a strategy for improving the competitiveness of elementary school students. The method used was a literature review, reviewing various relevant scientific sources. The results of the study indicate that the implementation of character education integrated into the learning process can foster discipline, responsibility, cooperation, and self-confidence in students. These values are crucial factors in enhancing students' adaptability and competitiveness amidst global competition. Furthermore, the success of character education depends not only on the school environment but also requires the active participation of families and communities. Therefore, the implementation of character education needs to be carried out consistently and sustainably to produce a generation that is not only intellectually superior but also possesses integrity and high competitiveness.